IMPLEMENTING TOTAL QUALITY MANAGEMENT APPROACH IN GARMENTS INDUSTRY - Syduzzaman, Syduzzaman; Rahman, Mahbubor; Islam, Mazedul; Habib, Ahashan; Ahmed, Sharif (European Scientific Journal, ESJ, 2014)
Rapid developments in international competition have obliged textile enterprises to take new approaches in order to gain a competitive advantage. The limits of acceptable quality levels for the enterprises have fallen back down to critical points due to the effects of liberal policies in international markets. Total Quality Management (TQM) keeps vital role in improving productivity, product quality and reduces manufacturing cost by reducing rework and scrape. TQM method has a great applicability in RMG sector. As RMG sector is the largest industrial sector of Bangladesh, Product Quality improvement can play a vital role in opening the doors of great opportunities for the country. To perform this study we take help of the tools of TQM such as Flow chart, Check sheet, Histogram, Pareto Chart, Scatter Diagram, Control Chart, Cause and effect diagram from various garment industries of Bangladesh to analyse collected data which were collected through observation method and it is found that a significant amount of rework and scrape per style, per month has minimized by applying this method. Implementing Total quality control applications are gaining in importance because the textile & apparel sector is a sector in which consumer expectations and preferences are of primary importance.